Overview of Community Empowerment throughBatik Tulis Training in Jorong Tabek, Solok District - Amelia, Rani Cantika; Sunarti, Vevi (Universitas Negeri Padang, 2024)
This research is motivated by the realization of community empowerment in Jorong Tabek, Solok Regency. This is presumably because the success of community empowerment cannot be separated from community participation in participating in batik activities. This study aims to describe community empowerment activities carried out in the form of developing, strengthening power as well as the potential and independence of the community in Jorong Tabek, Solok Regency. This research is included in the form of quantitative research with a descriptive type with a population of 36 people involved in batik training. Samples were obtained using a simple random sampling technique of 27 people, the data collection technique was a questionnaire, data analysis used a percentage formula. The results of the study showed that (1) the development activities carried out in community empowerment through written batik training in Jorong Tabek, Solok Regency, had gone very well. (2) Activities to strengthen the power and potential in community empowerment through written batik training in Jorong Tabek, Solok Regency, have gone very well. (3) Independent activities carried out in community empowerment through written batik training in Jorong Tabek, Solok Regency have gone very well.Keywords: Empowerment, Training, Written Batik